Perspektif Hukum Pidana Islam tentang Penyelesaian Masalah Kejahatan secara Rekonsiliatif - Muhammad Abdul Kholiq (Jurnal Hukum IUS QUIA IUSTUM, 2003)
In Perspective Law of Islamic Criminal, reconciliation has been familiar through the concept Al-a'fwu 'uquubah. Islamic Reconciliation is only relevant to the certain felony casesnamely qishash and it is different from jarimah hudud. The validity of reconciliation of Islam must be based on the certain requirements in order/hat the reconciliation created isthe problem solving and executable as well.